2011
DOI: 10.5039/agraria.v6i4a909
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do potencial agronômico de vermicomposto produzido a partir de lodo de esgoto doméstico

Abstract: O objetivo desta pesquisa foi avaliar o potencial agronômico de vermicomposto obtido a partir de lodo de esgoto doméstico e misturas de lodo de esgoto doméstico e solo, segundo os critérios do Ministério da Agricultura, Pecuária e Abastecimento (MAPA), visando ao seu uso sustentável, isto é, transformando um resíduo indesejável em um produto comercial com valor agregado. Os resultados obtidos para os vermicompostos produzidos, se comparados com as exigências de especificações, garantias e limites de contaminan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Dores-Silva et al (2011a, 2011b highlight that, in the vermicomposting process, part of the organic C starts to participate in the earthworm biomass and another Lopes et al (2008) indicate a value of organic C above 25% as ideal for substrates, and the generated vermicompost is slightly above the proportion considered as adequate. For the nutrients Mg and S, the contents did not change with the increment of DE, despite the low Mg content in the DE (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Dores-Silva et al (2011a, 2011b highlight that, in the vermicomposting process, part of the organic C starts to participate in the earthworm biomass and another Lopes et al (2008) indicate a value of organic C above 25% as ideal for substrates, and the generated vermicompost is slightly above the proportion considered as adequate. For the nutrients Mg and S, the contents did not change with the increment of DE, despite the low Mg content in the DE (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it has high water retention capacity. In a study by Silva et al (2011), when vermicomposting was applied in domestic sewage sludge with different soil concentrations, vermicomposting final humidity of 38,55% was obtained in the treatment with 100% domestic sludge; 32,19% in the treatment with 75% sludge and 25% soil; and 25,22% in the treatment with 50% sludge and 50% soil. It was observed that, in the extent to which soil concentration increased, moisture decreased.…”
Section: Resultsmentioning
confidence: 99%